Picture of MOTHER Based on Selected Writings of Vanda Juknaitė - Slotvinska, Karolina (Vilnius University Open Series, 2021)
The article provides the analysis of the linguistic picture of mother in contemporary Lithuanian literature. The analysis is based on the writings of contemporary Lithuanian writer Vanda Juknaitė, namely on her novella Stiklo šalis (‘Land of Glass’) and novel Šermenys (‘Funeral’). The research is carried out using cognitive linguistics methodology and the description of linguistic worldview in texts. Through multiple aspects and meanings, fragility, the author shows the real view of mother, with all her weaknesses and dark sides. mother is called using a very general word woman , which probably highlights the importance of maternity in each woman’s life. mother takes no care of her appearance: looks tired, dark, and sad. Her psychological world is full of contrasts; she is strong and weak, decisive and reluctant, brave and timid at the same time. However, she features very strong relations (both physical and psychological) with her child. The analysis of Juknaitė’s idiolect has shown that the author provides no idealised picture of mother.